Perlakuan Akuntansi Aset Tetap Berdasarkan Standar Akuntansi Pemerintahan Pernyataan Nomor 07 Pada Politeknik Negeri Bengkalis - Dari, Ulan; Mubarak, Husni (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2023)
The purpose of this study is to find out how the classification, recognition, measurement, depreciation, revocation and ownership, as well as disclosure of fixed assets based on PSAP No. 07 at Bengkalis State Polytechnic. Data collection techniques are observation, interviews and documentation. The results of this study indicate that most of the fixed asset accounting stages have carried out asset accounting treatment in accordance with PSAP 07 of 2010 which includes classification, recognition, measurement, depreciation, termination and accounting as well as accounting. However, there are still several obstacles in the classification, depreciation and the disclosure of fixed assets at the Bengkalis State Polytechnic so that it has not been carried out properly according to PSAP 07 of 2010.Keywords: Fixed Assets, PSAP No.07